Prostate cancer mortality in Brazil 1990-2019: geographical distribution and trends - Iser,Daniel Albrecht (2022)
Abstract INTRODUCTION: To analyze the trend of prostate cancer mortality in the Brazilian population of 40 years of age and above. METHODS: Time series ecological study of the mortality rates due to prostate cancer in men of 40 years of age and above, using data from the Global Burden of Disease 2019 (GBD). Age-standardized mortality rates were calculated, as well as the age-standardized rates by the GBD for the global population, per 100,000 inhabitants, for Brazil and its States, from 1990 to 2019. The annual average percent change (AAPC) was calculated to identify the mortality trends in Brazil, through linear regression using the Joinpoint Regression Program. RESULTS: The standardized rates of prostate cancer mortality in Brazil were 76.89 in 1990 and 74.96 deaths for every 100 thousand men ≥ 40 years of age in 2019, with a stability trend. By age group, it was observed a decreasing trend up to 79 years of age, and an increasing trend as of 80 years of age. The state of Bahia showed the highest increase in mortality in the period (1.2%/year), followed by Maranhão and Pernambuco (1.0 and 0.9%/year). A decrease of prostate cancer mortality was found in the Federal District, Goiás, Minas Gerais, Rio de Janeiro, Rio Grande do Sul, Roraima, Santa Catarina, São Paulo, and Sergipe. CONCLUSIONS: In Brazil, the standardized mortality rates show a trend toward stability from 1990 to 2019 and no pattern was observed for the trends according to the Brazilian States.